(untitled) - Lynch, Vincent J (Boston, 2000)
Includes bibliographical references and index; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: AIDS (Disease) -- Patients -- Care; AIDS (Disease) -- Social aspects; Social service; Social workers; AIDS (Bệnh tật) -- Khía cạnh xã hội; Dịch vụ xã hội